2013
DOI: 10.1177/1541931213571416
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Road Conditions on Driver Stress

Abstract: A number of studies have used heart rate variability (HRV) measures to estimate driver stress across different driving conditions. Understanding the constructs of driver stress can provide insights regarding the underlying reasons for safety-critical events. The intent of this study is to evaluate the electrocardiogram (ECG) activities of drivers along a pre-defined route with varying roadway conditions. Heart rate, standard deviation of selected RR interval series (SDNN) and low frequency to high frequency ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Some studies also show that HR value has an indirect relationship to driving time and a direct relationship to vehicle maneuvering, traffic volume, and road direction (Simonson et al 1968;Platt 1970). Compared with HR, HRV signals (both in time and frequency domains) retain their characteristics related to driver stress regardless of the direction of travel (Miller and Boyle 2013). However, HRV is shown to increase with driving time and decrease after alerting events.…”
Section: Heartmentioning
confidence: 96%
See 2 more Smart Citations
“…Some studies also show that HR value has an indirect relationship to driving time and a direct relationship to vehicle maneuvering, traffic volume, and road direction (Simonson et al 1968;Platt 1970). Compared with HR, HRV signals (both in time and frequency domains) retain their characteristics related to driver stress regardless of the direction of travel (Miller and Boyle 2013). However, HRV is shown to increase with driving time and decrease after alerting events.…”
Section: Heartmentioning
confidence: 96%
“…HRV signals are often analyzed in time and frequency domains to detect driver stress levels. In the time domain, HRV signals are indirectly related to driver stress (Eilebrecht et al 2012;Miller and Boyle 2013). Mean normal-to-normal intervals (MNN), standard deviation of normal-to-normal intervals (SDNN), square root of the mean squared difference of successive normal-to-normal intervals (RMSSD), and number of pairs of successive normal-to-normal intervals that differ by more than 50ms (PNN50) have been used by several studies as HRV time-domain features.…”
Section: Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable amount of research has been conducted to develop ways to detect threats during driving, with the main foci being on stress [17,22,23,24,25], fatigue [26,27,28], and aggressiveness [29,30,31,32,33]. These factors are linked to stressful driving situations and are associated with increased risk of fatal accidents [6].…”
Section: Related Workmentioning
confidence: 99%
“…Hayano et al [38] compared a driver’s heart rate to their estimated manipulations, such as accelerating, and found that it corresponded to the vehicle’s speed. These results suggest that heart rate is a strong indicator of physical state in situations on the road [24]. Healey et al [22] analyzed data from 24 driving sessions that were at least 50 min in length.…”
Section: Related Workmentioning
confidence: 99%